Impacts of combined sewer overflows on a large urban river – Understanding the effect of different management strategies. (15th November 2016) - Riechel, Mathias; Matzinger, Andreas; Pawlowsky-Reusing, Erika; Sonnenberg, Hauke; Uldack, Mathias; Heinzmann, Bernd; Caradot, Nicolas; von Seggern, Dörthe; Rouault, Pascale
Abstract: To support decision makers in planning effective combined sewer overflow (CSO) management strategies an integrated modelling and impact assessment approach has been developed and applied for a large urban area in Berlin, Germany. It consists of an urban drainage model, a river water quality model and a tool for the quantification of adverse dissolved oxygen (DO) conditions in the river, one of the main stressors for urban lowland rivers. The coupled model was calibrated successfully with average Nash-Sutcliffe-efficiencies for DO in the river of 0.61 and 0.70 for two validation years. Moreover, the whole range of observed DO concentrations after CSO down to 0 mg L −1 is simulated by the model. A local sensitivity analysis revealed that in the absence of CSO dissolved oxygen principally depends on phytoplankton dynamics. Regarding CSO impacts, it was shown that 97% of the observed DO deficit can be explained by the three processes (i) mixing of river water with CSO spill water poor in DO, (ii) reduced phytoplankton activity due to CSO-induced turbidity and (iii) degradation of organic matter by heterotrophic bacteria. As expected, process (iii) turned out to be the most important one. However depending on the time lag after CSO the other processes can become dominant. Given the different involved processes, we found that different mitigation schemes tested in a scenario analysis can reduce the occurrence of critical DO deficits in the river by 30–70%. Overall, the study demonstrates that integrated sewer-river-models can be set up to represent CSO impacts under complex urban conditions. However, a significant effort in monitoring and modelling is a requisite for achieving reliable results. Graphical abstract: Highlights: An integrated CSO impact model has been set up for a large urban area. Different processes contributing to acute oxygen stress after CSO are quantified. Based on the process analysis suitable mitigation measures can be selected. The tested measures can reduce the occurrence of critical DO deficits by up to 70%. The model tool is ready to be used for strategic planning at city-scale.